Eggplant turbinoplasty: how I do it - Mosaad Abdel-Aziz; Ahmed Nassar; Ahmed Ibrahim Yousef; Omar Aly Sabry (The Egyptian Journal of Otolaryngology)
Key points 1. The inferior turbinate is a static structure with a dynamic function as it plays a major role in the formation of nasal valve and laminar airflow. 2. The inferior turbinate resembles an eggplant: it has head, body, and tail; and it is formed of 3 layers which are an outer covering mucosa, an intermediate submucosal connective tissue, and an inner bony concha. 3. Eggplant turbinoplasty technique involves removal of the infero-lateral part of the inferior turbinate longitudinally. 4. The excised part consists of soft tissue and bone, and the raw area is covered with a medial soft tissue flap. 5. The medial turbinate mucosa is preserved which is very important for warming and humidification of the inspired air. 6. The procedure decreases the size of the turbinate without major changes in the shape to maintain the laminar airflow. 7. Intraoperative bleeding is usually minimal as the inferior turbinate artery enters the turbinate through its upper surface. 8. Postoperative crustations is avoided as the raw area is completely covered with a medial soft tissue flap. 9. The procedure does not need special equipments. 10. This turbinate reduction technique respects both the anatomical shape to maintain normal laminar airflow, and the physiologic concepts with preserving the medial mucosa for airway protection.